2020
DOI: 10.1002/osp4.448
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers/facilitators to a healthy lifestyle among diverse adolescents with overweight/obesity: A qualitative study

Abstract: Objective: Effectiveness of behavioural obesity treatments in adolescents is modest. Thus, incorporating participant feedback may lead to improvement of intervention acceptability. This qualitative study's objective was to assess perceived barriers/facilitators to weight loss and healthy lifestyles among diverse adolescents with overweight/obesity (OW/OB). Methods: Adolescents ages 14-19 with BMI ≥ 85th percentile participated in focus groups and identified perceived barriers/facilitators to weight loss and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…The evidence in this study suggests that participants grasped the drivers of malnutrition but did not identify malnutrition as a complex health issue involving structural determinants such as political, geographical and socioeconomic factors. Consistent with qualitative evidence in adolescents, this study identified malnutrition drivers to be sanitation [ 52 , 53 ], exercise [ 54 ], families [ 55 ], peers [ 56 ], wellbeing [ 57 , 58 ], gender [ 59 , 60 ], nutritional knowledge [ 61 ], media [ 56 ], and most importantly, food [ 59 , 62 ]. Malnutrition appeared to be strongly linked to dietary intake and eating habits in this sample.…”
Section: Discussionsupporting
confidence: 54%
“…The evidence in this study suggests that participants grasped the drivers of malnutrition but did not identify malnutrition as a complex health issue involving structural determinants such as political, geographical and socioeconomic factors. Consistent with qualitative evidence in adolescents, this study identified malnutrition drivers to be sanitation [ 52 , 53 ], exercise [ 54 ], families [ 55 ], peers [ 56 ], wellbeing [ 57 , 58 ], gender [ 59 , 60 ], nutritional knowledge [ 61 ], media [ 56 ], and most importantly, food [ 59 , 62 ]. Malnutrition appeared to be strongly linked to dietary intake and eating habits in this sample.…”
Section: Discussionsupporting
confidence: 54%
“…The blood samples were centrifuged at 3000 rpm for 10 min; after being separated from the whole blood, the serum was stored at a temperature of -80°C until clinical chemistry analysis was run. Liver function tests such as aspartate transaminase (AST), alanine transaminase, alkaline phosphatase (ALP), albumin, and bilirubin total (BILT); enzyme tests such as α -amylase (AMYL) and lipase [ 28 ]; and heart function tests such as C-reactive protein (CRP), highly sensitive (CRP-HS), troponin, and creatine kinase (CK) were conducted. In addition, kidney function tests like urea and creatine were examined according to analysis parameters indicated in [ 1 , 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Adolescent engagement in self-directed strategies to manage weight may be influenced by parents, peers, and the media. Adolescents report feeling shame and guilt when parents comment on their weight (43), and parental weight-related teasing is associated with engagement in binge eating and purging behaviors and weight gain in adolescents (44). Similarly, bullying by peers is associated with body shame and disordered eating behaviors (45).…”
Section: External Influencesmentioning
confidence: 99%